One-step fabrication of polymeric self-solidifying ionic liquids as the efficient catalysts for biodiesel production. (10th April 2021) - Lin, Xiaocheng; Li, Mantian; Chen, Zhiwen; Li, Meichen; Huang, Youjie; Qiu, Ting
Abstract: Polymeric self-solidifying ionic liquids (PSILs) were simply fabricated by the facile nucleophilic substitution reaction between polyethyleneimine (PEI) and 1, 3-propanesultone (PS). Because of the presence of less-substituted amino groups in PEI chain, more than 1 equivalents of sulfonic groups (–SO3 H) per amino group were grafted onto PEI chain. Part of –SO3 H groups could be bonded with amino groups to form –SO3 – …N + – zwitterions, the presence of zwitterion and the high molecular of PEI could make PSILs become solid, while the left free –SO3 H groups played a role in the acid catalysis and therefore no additional acids were required. The final PSILs showed high catalytic activity, stability and generality as the heterogeneous catalysts for biodiesel production via the esterification of a variety of free fatty acids (FFAs), as well as the transesterification of waste cooking oil and palm oil. Moreover, the one-step fabrication process of PSILs is much simpler than the multi-step fabrication process of traditional ionic liquids, suggesting potential benefits. Highlights: Heterogeneous acidic polymeric self-solidifying ionic liquids are synthesized. The synthesis process is simple and requires no additional acids and supports. The ionic liquids have high catalytic activity for biodiesel production. The reusability of polymeric self-solidifying ionic liquids is good.